2008
DOI: 10.1111/j.1365-2923.2008.03146.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching doctors how to diagnose paroxysmal events: a comparison of two educational methods

Abstract: The computerised tutorial more effectively imparted knowledge immediately post-teaching. However, facilitated case discussion is the preferred modality in terms of participant enjoyment and perceived usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 22 publications
1
31
0
Order By: Relevance
“…Supporting previous research, 2–5 we have shown computerised tutorial to be as effective as face‐to‐face teaching in promoting knowledge acquisition 6 . In contrast to others who used multiple choice questioning to evaluate learning, 2–5 our research employed a comprehensive score based on history taking to assess knowledge, mimicking the clinical consultation.…”
Section: Introductionsupporting
confidence: 55%
See 1 more Smart Citation
“…Supporting previous research, 2–5 we have shown computerised tutorial to be as effective as face‐to‐face teaching in promoting knowledge acquisition 6 . In contrast to others who used multiple choice questioning to evaluate learning, 2–5 our research employed a comprehensive score based on history taking to assess knowledge, mimicking the clinical consultation.…”
Section: Introductionsupporting
confidence: 55%
“…Farrar et al. 6 showed that medical staff recorded facilitated case discussion as a more enjoyable and effective teaching modality. Students in the current study also rated the interactive lecture more engaging, enjoyable and effective in teaching observation and clinical reasoning skills.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of use of PNES videos may be due to ethical concerns on posting these videos on the web. A related method is computerised tutorials, but these methods have not been designed to aid visual diagnosis of ES and PNES 26 27…”
Section: Discussionmentioning
confidence: 99%
“… Self‐rated measures of confidence regarding clinical approach to the child with a first unprovoked seizure and satisfaction with instruction were administered pre‐ and post‐teaching based upon scales previously used in other studies . A series of statements was presented with responses entered on a 5‐point Likert‐type scale ranging from 1 ( strongly disagree ) to 5 ( strongly agree ).…”
Section: Methodsmentioning
confidence: 99%